Two Novel AP2/EREBP Transcription Factor Genes TaPARG Have Pleiotropic Functions on Plant Architecture and Yield-Related Traits in Common Wheat - Li, Bo; Li, Qiaoru; Mao, Xinguo; Li, Ang; Wang, Jingyi; Chang, Xiaoping; Hao, Chenyang; Zhang, Xueyong; Jing, Ruilian (Frontiers in Plant Science, 2016)
AP2/EREBPs play significant roles in plant growth and development. The novel, pleiotropic TaPARG (PLANT ARCHITECTURE-RELATED GENE), a member of the AP2/EREBP transcription factor gene family, and its flanking sequences were isolated in wheat (Triticum aestivum L.). Two TaPARG genes were identified and named as TaPARG-2A and TaPARG-2D. Their amino acid sequences were highly similar especially in the functional domains. TaPARG-2A on chromosome 2A was flanked by markers Xwmc63 and Xgwm372. TaPARG-2D was mapped to chromosome 2D. Subcellular localization revealed that TaPARG-2D was localized in the nucleus. The results of tissue expression pattern, overexpression in rice, association analysis and distinct population verification jointly revealed that TaPARG functions during the entire growth cycle of wheat. Its functions include regulation of plant architecture-related and yield-related traits. Association analysis, geographic distribution and allelic frequencies suggested that favored haplotypes Hap-2A-2 and Hap-2A-3 were selected in Chinese wheat breeding programs. Both favored haplotypes might be caused by a single amino acid substitution (His/Tyr). These results suggest that TaPARG is a regulatory factor in plant growth and development, and that the favored alleles might be useful for improving plant architecture and grain yield of wheat.